Valor económico del volumen maderable y valor económico del secuestro de CO2 en un bosque de terraza baja del distrito del Napo, Loreto. 2022 - Acuña Ruiz, Narhely Yajaira (2022)
The economic values of the timber volume and the CO2 sequestration service of the commercial forest species in the low terrace forest, Napo district, Loreto, Peru, were compared in this study. Data from the forest census of PC1 for forest use permits in native communities and peasant communities were evaluated. The results show that the timber economic value amounts to USD 97 136,72 (USD/ha 123,54). Maquira coriacea (USD/ha 112,12 y USD 88158,34), Eschweilera coriacea (USD/ha 5,26 y USD 4136,02) and Vochysia vismiifolia (USD/ha 3,84 y USD 3022,68), have higher economic value; while; Virola albidiflora (USD/ha 1,29 y USD 1012,87), Ocotea cernua (USD/ha 0,58 y USD 458,79) and Hymenaea oblongifolia (USD/ha 0,44 y USD 348,02) have lower economic value. The economic value of CO2 sequestration is USD 694 825,79 (USD/ha 883,70). Maquira coriacea (USD 631 555,60, USD/ha 803,23), Eschweilera coriacea (USD 34 973,02, USD/ha 44,48) and Vochysia vismiifolia (USD 19879,17, USD/ha 25,28) report higher economic value; while Virola albidiflora (USD 7359,10, USD/ha 4,55), Hymenaea oblongifolia (USD 2861,04, USD/ha 3,64) and Ocotea cernua (USD 1977,87, USD/ha 2,52) present the lowest value. Statistically, there is no significant difference (? = 0,05) between the averages of the economic value of the timber volume and the economic value of CO2 sequestration was found..